The Value Chain Analysis to Support Industrial Cluster Development of Oil Palm-Cattle Integration in Pelalawan Regency - Kristiana Kristiana; Zulfika Satria Kusharsanto; Ramos Hutapea (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
As a region with the largest oil palm plantations in Indonesia, Pelalawan Regency is highly potential to develop a program of oil palm-cattle integration. Pelalawan has implemented the program legitimated by Regent Decree Number KPTS./524/Disnak/2012/472 regarding Zoning Regulation on the development of Oil Palm-Cattle Integration. The program of oil palm-cattle integration itself has been the basis for the Decree of the Minister of Agriculture Number 105 Year 2014 regarding the Integration of Oil Palm Plantation and Beef Cattle Farming. Moreover, the integration system of oil palm-cattle gives a lot of benefit to farmers, for example the utilization of manure as organic fertilizers could reduce farmer’s expenses for chemical fertilizers and the cattle can be an asset for them. Products made from the integrated program are solid manure, liquid organic fertilizer, fodder, biogas, and beef. To improve the competitiveness of those activities, we can analyze the value chain which includes product design, inbound logistics, operations, outbound logistics, marketing, sales, services and supporting activities. By using a value chain analysis, this study aims to provide recommendations for strengthening programs which could be implemented to improve the value-added of the products. Keywords: oil palm-cattle integration, value chain, value-added, industrial cluster